Association of nephrolithiasis with the risk of cardiovascular diseases: a longitudinal follow-up study using a national health screening cohort - Hyo Geun Choi; So Young Kim; Chanyang Min; Woo Jin Bang (BMJ Open)
Objectives The aim of this study was to explore the associations of stroke and ischaemic heart disease in patients with nephrolithiasis.Design A longitudinal follow-up study.Setting Data from the Korean National Health Insurance Service–Health Screening Cohort (2002–2013) were retrieved to identify the occurrence of nephrolithiasis.Participants and interventions In total, 19 103 patients with nephrolithiasis were matched at a 1:4 ratio with control participants for age, sex, income and region of residence.Primary and secondary outcome measures The occurrence of stroke and ischaemic heart disease was analysed in both patients with nephrolithiasis and control participants. The primary outcome was HRs of stroke and ischaemic heart disease in a stratified Cox proportional hazards model. Smoking, alcohol consumption, obesity and Charlson Comorbidity Index were adjusted for as covariates. Subgroup analyses according to age and sex were also performed.Results Eight per cent (1615/19 103) of patients with nephrolithiasis and 7.2% (5476/76 412) of control participants had stroke. Nine per cent (1879/19 103) of patients with nephrolithiasis and 7.7% (5895/76 412) of control participants had ischaemic heart disease. Patients with nephrolithiasis had risks of stroke and ischaemic heart disease that were 1.18 times (95% CI=1.11 to 1.24) and 1.24 times (95% CI=1.18 to 1.31) those of the control participants, respectively. The age and sex subgroups showed consistent results.Conclusions Nephrolithiasis was associated with increased risks of stroke and ischaemic heart disease.